Framing the Latin American nutrition transition in a historical perspective, 1850 to the present - Jonathan D. Ablard (História, Ciências, Saúde: Manguinhos)
Abstract This paper argues that many of the foundations and trends that led to the rise in obesity and other diet-related health problems in Latin America began to develop in the late nineteenth century. The tendency towards presentism in the nutrition transition literature provides a much abbreviated and limited history of changes in diet and weight. Whereas medical and nutrition researchers have tended to emphasize the recent onset of the crisis, a historical perspective suggests that increasingly global food sourcing prompted changes in foodways and a gradual “fattening” of Latin America. This paper also provides a methodological and historiographic exploration of how to historicize the nutrition transition, drawing on a diverse array of sources from pre-1980 to the present.